2011
DOI: 10.2478/v10172-011-0013-0
|View full text |Cite
|
Sign up to set email alerts
|

Determination Brittle Temperature Range of Msr-B Magnesium Alloy

Abstract: Magnesium alloys are a part of a group of lightweight and ultra-lightweight alloys, which are important in practical use in constructions. Due to the development of these alloys, they are currently used in many fields of science and their maximum working temperature is about 250˚C. Nowadays, magnesium alloys are used for casting into sand moulds of huge dimensional castings, high-pressure castings and precise casings. In castings of magnesium alloys defects or inconsistencies (such as casting misruns, porositi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 2 publications
0
1
0
Order By: Relevance
“…The mean plane section area of grains in this case is equal to Ᾱ=830 µm 2 . In the specimens cast after other melting operations the mean plane section area of grains was equal to Ᾱ=1638-1871 µm 2 . The Mann-Whitney U-Test confirmed that the mean plane section area of grains is significantly different only in the specimen no.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mean plane section area of grains in this case is equal to Ᾱ=830 µm 2 . In the specimens cast after other melting operations the mean plane section area of grains was equal to Ᾱ=1638-1871 µm 2 . The Mann-Whitney U-Test confirmed that the mean plane section area of grains is significantly different only in the specimen no.…”
Section: Discussionmentioning
confidence: 99%
“…Elements such as engine housings, transmission cases, steering wheels etc. are more and more often produced from Mg alloys by means of sand casting or high-pressure die casting [1,2]. The commercial casting alloys containing aluminum (the AZ or AM system) offer good combination of high strength and corrosion resistance.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we determined the BTR of an Mg-Y-Zn alloy using hot tensile tests in a Gleeble system that allows the ductility and strength of the alloy to be measured at different temperatures and under conditions close to a real forming process. 36,43 The material under study was Mg 97 Y 2 Zn 1 containing 2 at% (6.8 wt%) Y and 1 at% (2.5 wt%) Zn. In this material, LPSO phases form that are responsible for exceptionally good mechanical properties up to high temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Under the heat treatment, the morphology of the precipitates of the (Mg,Ag) 12 Nd phase changes (fig. 1b) [6]. Welding and pad welding of magnesium alloys is applied as a method of repairing defects occurring after the casting process: cracks, micro-shrinkages, etc.…”
Section: Introductionmentioning
confidence: 99%
“…The most frequent reason for rejecting the repaired cast or construction are the cracks occurring during the welding process. The QE22 alloy exhibits the best weldability after casting [6,7]. An important factor determining the validity of application of welding techniques for repairing or joining the cast magnesium alloys is the structural stability and the stability of the properties of the joint in operating conditions.…”
Section: Introductionmentioning
confidence: 99%